Is Industry 4.0 a Good Fit for High Performance Work Systems? Trade Unions and Workplace Change in the Southern Ontario Automotive Assembly Sector - Rutherford, Tod; Frangi, Lorenzo (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
The automotive industry has long been a leader in the introduction of new forms of work organization and technology—including mass production and high performance work systems (HPWS). It has also been a focal point for how trade unions negotiate such systems. Recently, much attention has focused on Industry 4.0 (I 4.0)—a manufacturing system featuring advanced robotics, digitalization and artificial intelligence. However, in the automotive industry, I 4.0 is confronted with considerable technical and social challenges, and I 4.0 paradigms have been criticized for marginalizing the continuing importance of employees in shaping, if not ‘hybridizing,’ such new production processes.Based on a study of UNIFOR union locals in Canadian automotive assembly plants, we argue that I 4.0 has to be analyzed in terms of the ways unions have influenced the almost universal adoption of HPWS in that sector. We thus investigate the ways unions have impacted HPWS and its implications for their roles in workplace integration of I 4.0. As such, we first argue that, while overlapping, HPWS and I 4.0 represent different managerial strategies. Second, we develop an exploratory analytical framework for use in examining union roles in negotiating HPWS and technology adoption.Based on this framework, we then analyze 18 interviews we conducted in 2017-2018 with plant managers and key UNIFOR representatives at five southern Ontario assembly plants. The interviews illustrate not only commonalities in adoption of HPWS, but also differing ways in which the union influences the ‘hybridization’ of HPWS. Union practices differ significantly from one plant to another as a function of three variables: 1- firm-plant competitive positions; 2- the union’s overall monopoly face; and 3- internal union local solidarity and narratives around HPWS. Keeping these commonalities and differences in mind, we then consider the challenges that unions are likely to confront as they begin negotiating I 4.0.